Production of indole acetic acid (bioauxin) from Azotobacter sp. isolate and its effect on callus induction of Dieffenbachia maculata cv. Marianne - El-Mahrouk, Mohammed Elsayed; Belal, E. B. A. (Acta Biologica Szegediensis, 2007)
lndole-3-acetic acid (IAA) in the supernatant of a culture from the strains, Rhizobium leguminosarum biovar viciae, Bradyrhizobium japonicum, Pseudomonas sp. and Azotobacter sp was detected. Azotobacter sp yielded the highest concentrations of IAA. It was shown that the indole-3-acetic acid (IAA) was induced by the presence of tryptophan, which is used as inducer because the plánt provide the bacteria with tryptophan under natural condi-tions. The highest concentration of IAA was produced by Azotobacter sp.(A1) at the end of the logarithmic phase (after 3days). The results obtained in this work provide useful information about the production behavior of IAA under the optimál conditions(temperature 30°C and pH 7) which is of importance fór the application in production Dieffenbachia maculat cv. Marianne plants by using tissue culture technique. This work was alsó conducted to study the effect of somé growth regulators such as 10 mg/l IAA (synthetic), 5 mg/l BA and 10 mg/l IAA (bioauxin) on callus formation of Dieffenbachia maculat cv. Marianne shoot tips and internodal segments were taken from sterilized shoot and cultured on MS médium supplemented with 6 different treatments from growth regulators. Explants cultured on MS médium supplemented with either 10 mg/l IAA +5 mg/l BA or 10 mg/l bioauxin + 5 mg/l BA had the highest callus percentage 97.22 and 93.94%, respectively. MS médium supplemented with 2 mg/l BA + 0.06 mg/l BA was used for callus differentiation.